Vortex fluidic mediated transformation of graphite into highly conducting graphene scrolls - Vimalanathan, K.; Suarez-Martinez, Irene; Peiris, M. Chandramalika; Antonio, Joshua; de Tomas, Carla; Zou, Y.; Zou, J.; Duan, X.; Lamb, R.N.; Harvey, D.P.; Alharbi, T.M.D.; Gibson, C.T.; et al. (ROYAL SOC CHEMISTRY, 2019)
Two-dimensional graphene has remarkable properties that are revolutionary in many applications. Scrolling monolayer graphene with precise tunability would create further potential for niche applications but this has proved challenging. We have now established the ability to fabricate monolayer graphene scrolls in high yield directly from graphite flakes under non-equilibrium conditions at room temperature in dynamic thin films of liquid. Using conductive atomic force microscopy we demonstrate that the graphene scrolls form highly conducting electrical contacts to highly oriented pyrolytic graphite (HOPG). These highly conducting graphite-graphene contacts are attractive for the fabrication of interconnects in microcircuits and align with the increasing interest in building all sp2-carbon circuits. Above a temperature of 450 °C the scrolls unravel into buckled graphene sheets, and this process is understood on a theoretical basis. These findings augur well for new applications, in particular for incorporating the scrolls into miniaturized electronic devices.